Presence of Alcohol, Cocaine, and Other Drugs in Suicide and Motor Vehicle Crash Decedents Ages 18 to 54. (27th January 2017) - Conner, Kenneth R.; Lathrop, Sarah; Caetano, Raul; Wiegand, Timothy; Kaukeinen, Kimberly; Nolte, Kurt B.
Abstract : Background: Use of alcohol and select other drugs confer risk for injury deaths, yet how such use compares in different types of injury deaths including suicide and fatal motor vehicle collisions (MVCs) is unclear. Methods: Individuals in New Mexico ages 18 to 54 that died in 2012 by suicide or MVC were analyzed. Toxicology results were used to code the presence of alcohol and the presence of 1 or more drugs including cocaine, opiate (oxycodone, heroin, etc.), or amphetamine or methamphetamine, yielding a 4‐category variable: Alcohol + Drug, Alcohol (without drug), Drug (without alcohol), and Neither (ref). Suicides were compared to MVCs (ref) using unconditional logistic regression analyses adjusted for sex, age, and ethnicity. Poisoning suicides were removed prior to analyses to exclude cases where the drugs may have been used to hasten death. Results: Analyses were based on 185 suicides and 161 MVCs. Alcohol + Drug was more likely in suicide decedents, AOR (95% CI) = 4.33 (1.70, 11.03). Alcohol (without drug) and Drug (without alcohol) did not differ between the groups. Uniquely, all suicides that were positive for cocaine were also positive for alcohol. As follow‐up, similar results were obtained in a post hoc analysis that limited the drug exposure variable to cocaine: Alcohol + Cocaine, AOR (95% CI) = 4.69 (1.59, 13.88). Conclusions: The co‐presence of alcohol and 1 or more drugs of abuse, particularly cocaine, may be more likely in suicide deaths compared to MVCs. Results may inform prevention efforts targeting specific substances and types of injury. Abstract : Toxicology results of individuals in New Mexico ages 18–54 that died in 2012 by suicide ( n  = 185) or motor vehicle collision, MVC ( n  = 161), were compared. After statistical adjustment for age, sex, and ethnicity, the co‐presence of alcohol and another drug of abuse (Alcohol + Drug) was more likely in suicides compared to MVCs. There was elevated co‐presence of alcohol and cocaine in particular, leading to the hypothesis that alcohol and cocaine in combination may play a role in suicide.